Using of marketing tools in the restaurant business - Китченко, Елена Николаевна; Чемерис, Ангелина Владимировна (Technology audit and production reserves, 2017)
The problems related to the use of marketing tools in the restaurant market are considered. Particular relevance these problems have in the foodservice sector, where today there is a huge competition and only restaurants, which make full use of the entire range of marketing techniques, may survive. The brief overview of the development of the restaurant business market in Ukraine in recent years is done. Six main segments that characterize the restaurant market in Kharkiv are identified (premium, middle segment, low segment, segment of restaurants for the whole family, country restaurant complexes, and coffee shops). It is determined that the greater success in the market in Kharkiv have the chain restaurants, they are the headliners and innovators in the field of advertising and PR. It is identified a number of steps that require special attention at the opening the restaurant. It is found that a clear understanding and drawing the portrait of a consumer enables the use of promotional funds more efficiently. Principles and promotion tools are revealed depending on the restaurant’s life cycle. The analysis makes it possible to focus of restaurateurs on the need of a clear understanding and description of the portrait of a consumer, and also makes it possible to structure and define the mechanism and selection of marketing tools at the opening the restaurant.